Selection of nest sites by wood mice Apodemus sylvaticus in a Mediterranean agro-forest landscape (Ecological Research, 2011)
One of the most important structures for an individual’s survival is a refuge, especially for species subject to signiﬁcant predatory pressure or living in environments aﬀected by severe climatic conditions. We studied how wood mice (Apodemus sylvaticus), inhabiting a Mediterranean environment, use nests and the factors that could be determining this use. Radiotracking of 16 mice allowed us to detect 24 diurnal nests, which were used with a high ﬁdelity rate (1.75 nests/ animal). Nest sites that had been identiﬁed using radiotracking were matched with 24 randomly selected nonnest sites (located within an area deﬁned by the sum of all individual home ranges), and all sites were characterized according to their macro- and micro-habitat parameters. Using a generalized linear model, we tested three hypotheses: (1) a nest’s use is inﬂuenced by its proximity to food patches; (2) the degree of sheltering provided by each site inﬂuences its use; and (3) nest use is constrained by a combination of food- and shelterrelated features. Females had higher nest ﬁdelity than males, and the degree of sheltering provided by each site had a positive signiﬁcant inﬂuence on its use. Nests oﬀering higher protection (e.g., under thick vegetation), good drainage (e.g., sleep slopes), and lower human and predatory disturbance (far from orchards) were most often used. The proximity to food patches seemed to negatively inﬂuence nest use. Results indicate the need to preserve patches of natural dense vegetation near riparian habitats, which is in agreement with the focus of mammalian protection plans in Mediterranean agricultural landscapes. These patches are important areas for Apodemus sylvaticus, an acorn disperser species, which is preyed on by raptors and mammalian carnivores.